Structure and Electrical Properties of Lead-free Piezoelectric Ceramics Bi0.5Na0.5TiO3-Ba0.94Sr0.06(Sn0.08Ti0.92)O3 - Yin, Qiyi; Sun, Zhaoqi; Shi, Shiwei; Yang, Jie; Tian, Changan; Bao, Meiling (Asian Journal of Chemistry, 2014)
New lead-free piezoelectric ceramics BNBSST-100x have been prepared by the traditional solid state sintering technique and systematically studied. The results of XRD confirm that all ceramics samples possess pure perovskite structure, showing that the morphotropic phase boundary between rhombohedral and tetragonal phase of the ceramics locates in the range of 0.02 < x < 0.06. The BNBSST-4 ceramic samples near the morphotropic phase boundary exhibits improved properties, which are d33 = 203pC/N, kp = 41 %, er = 1128, tan q = 2.6 %, Pr = 35.6 μC/cm2 and EC = 3.51 kV/mm, suggesting that the ceramics are suitable for future application.